Molecular Characterization of Glycopeptide-Resistant Enterococci from Hospitals of the Picardy Region (France). (31st October 2010) - Biendo, M.; Adjidé, C.; Castelain, S.; Belmekki, M.; Rousseau, F.; Slama, M.; Ganry, O.; Schmit, J. L.; Eb, F.
Abstract : We studied 138 glycopeptide-resistant enterococci (GRE) strains, consisting of 131 glycopeptide-resistant Enterococcus faecium (GREfm) and 7 glycopeptide-resistant Enterococcus faecalis (GREfs). The GREfm strains were resistant to penicillin, ampicillin, vancomycin, and teicoplanin, while the GREfs strains were only resistant to vancomycin and teicoplanin. The van A gene was the only glycopeptide determinant present in all GRE isolates investigated. Genes coding for Hyl and Hyl+ Esp were detected in 39 (29.8%) and 92 (70.2%) of the 131 GREfm isolates, respectively. Three of the 7 GREfs were positive for gelE + asa 1 genes, 3 for gel E gene, and 1 for asa 1 gene. The genetic relationship between the 138 GRE was analyzed by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). GREfm isolates were clustered in a single genogroup (pulsotype A), and GREfs were clustered in six genogroups (pulsotypes B-G). Among the isolates investigated by MLST, only 18 PCR products were sequenced (12 E. faecium and 6 E. faecalis ), and 9 sequence types (STs) were identified.